Prevention of Malaria Cases in Trenggalek District Based on The Epidemiological Triangle of East Java Province Year 2012-2017 - Ratu Ulani; Nurhikmadani; Rahmattika; Novita Sari; Reyza Harani (Journal of Health Science and Pharmacy, 2026)
Background: Indonesia has a large Muslim population, with a substantial proportion residing in areas that are vulnerable to malaria transmission. One such area is Trenggalek District, which is classified as a malaria-endemic region in East Java Province. Geographical conditions, occupational activities, and population mobility are factors that may influence malaria transmission dynamics in this region. Methods: This study employed a descriptive observational research design. Secondary data were obtained from the Environmental Health Engineering and Disease Control Agency (BBTKLPP) Surabaya. The data included information on the characteristics of malaria cases in Trenggalek District as well as the results of resistance testing of Anopheles vagus mosquitoes to 0.75% permethrin insecticide conducted in Pandean Village, Trenggalek District. Results: Trenggalek District is categorized as a low malaria endemic area, with most reported cases being imported, as no indigenous malaria cases have been identified to date. Malaria case trends from 2014 to 2017 exhibited fluctuating patterns. The majority of malaria patients were male (97.34%), with 59.88% working as farmers and 29.79% employed in the private sector. The insecticide resistance test showed that 100% of Anopheles vagus mosquitoes died within one hour of exposure to 0.75% permethrin, while no mortality was observed in the control group. Conclusion: Most malaria cases in Trenggalek District occurred among male individuals with high mobility, particularly those working as farmers or in the private sector, indicating a potential risk for the emergence of indigenous malaria transmission. Anopheles vagus mosquitoes in Pandean Village, Trenggalek District, remain susceptible to 0.75% permethrin insecticide. Keywords: Malaria cases; Trenggalek District; East Java; Anopheles vagus; permethrin resistance